Implementation of the Independent Curriculum For Early Childhood Education at TK Plus El-Huriyah North Cikarang - Muhamad Farhan Amien; Angga Fermana Kautsar; Deni Ardian; Ega Trisna Rahayu; Rolly Afrinaldi (UNIVERSITAS NEGERI MAKASSAR, 2024)
This research aims to find out how the independent curriculum is implemented at the kindergarten level. The research uses descriptive qualitative methods with data collection techniques carried out using documentary methods, literature studies, observations and surveys. The Indonesian curriculum is undergoing a transition period from the thirteenth curriculum to the independent curriculum. During this transition period, all elements of education are adapting to the use of this new implementation. Starting from preparing changes to educational administration to implementing learning in the classroom. There are many obstacles to be faced and all implementers in the field are expected to innovate to maximize this independent curriculum. One of the levels of education that implements the independent curriculum is the kindergarten level. At the kindergarten level, the implementation of the independent curriculum is still very complicated because it has to adapt to students' understanding of learning. Researchers conducted observations at the Plus El-Huriyah Kindergarten school and found innovative learning in movement learning, namely the use of educational game learning media called APE. The use of APE in learning is carried out in a mentoring manner, making students carry out movement learning freely, measurably and efficiently. However, the problem is that teachers have to update their APE learning media every week because they remember that the age of students is easily bored and APE is not yet optimal. All parties must work together to maximize the implementation of this independent curriculum.